Manajemen Komunikasi CSR Dalam Membentuk Brand Image Perusahaan PT. Cahaya Gaharu Kabupaten Langkat - Fahada, Adjie Imam; Hardiyanto, Sigit (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2023)
A company that sells a product will fail without a strategy to create a positive image in society. This research aims to provide an overview of CSR (Corporate Social Responsibility) communication management carried out by PT. Cahaya Gaharu Langkat in forming a brand image. This research aims to provide an overview of CSR Communication Management in Forming the Brand Image of the PT Company. Cahaya Gaharu Langkat Regency, the theories that are considered relevant are regarding Communication Management, CSR Communication and Brand Image. The research method used is descriptive qualitative. The data collection technique used is observation, interviews and documentation. The analysis techniques used include data reduction/data sorting, data presentation, drawing conclusions and verification. The informants for this research consisted of company leaders, company public relations and an employee. The research results show that PT. Cahaya Gaharu Langkat carries out community empowerment through CSR programs, such as opening employment opportunities and involving local communities in gaharu cultivation, the company creates prosperity for local communities. Apart from that, it also creates enthusiasm to preserve gaharu and sustainable natural resources so that we can experience the benefits together